The impact of the mortgage interest and capital deduction scheme on the Belgian mortgage market - Annelies Hoebeeck; Koen Inghelbrecht (National Bank of Belgium, 2017)
In 2005, mortgage interest, capital deductions and insurance premiums (MICPD) were assembled into one single deduction package to further stimulate home ownership in Belgium. Former research has shown that the MICPD did not raise the probability of becoming a home owner, due to its capitalisation into higher house prices. The objective of this paper is to investigate how the transmission of the capitalisation takes place. The analysis is based on data extracted from the Household Finance and Consumption Survey. The mortgage amount, the mortgage maturity, the interest rate and the house price are estimated simultaneously using a 3-SLS approach. The results suggest that the mortgage deduction does not result in more affordable housing by shortening the mortgage maturity. Most likely, the mortgage deduction results in larger amounts being borrowed, which in turn may indirectly push up house prices, the mortgage maturity and the interest rate as well. Although our estimation sample is rather small, these results suggest that the MICPD might be more beneficial for sellers and mortgage-granting institutions than for home owners.
Keywords: G21; H24; H31; 330; Mortgages; tax policy; house prices; mortgage interest deduction; household borrowing